HUBUNGAN KONSUMSI FATTENING FOODS DENGAN RASIO LINGKAR PINGGANG PINGGUL (RLPP) DAN BODY ROUNDESS INDEX (BRI) PADA REMAJA DI SMA NEGRI SURAKARTA - Riska Ariana; Dyah Intan Puspitasari; Firmansyah Firmansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Central obesity among adolescents has become an increasingly important public health issue due to changes in dietary patterns and modern lifestyles. Consumption of fattening foods, such as fast food, fried foods, high-sugar foods, and high-fat foods, is suspected to contribute to increased body fat distribution, as measured by the Waist-to-Hip Ratio (WHR) and Body Roundness Index (BRI). This study aimed to analyze the relationship between fattening food consumption and WHR and BRI among adolescents in public senior high schools in Surakarta. This analytical observational study employed a cross-sectional design involving 140 respondents selected using a multistage random sampling technique from four public senior high schools in Surakarta. Data on fattening food consumption were collected using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), while WHR and BRI were assessed through anthropometric measurements of waist circumference, hip circumference, and height. Data were analyzed descriptively and bivariately using the Pearson Product-Moment or Spearman Rank correlation test according to data distribution. The results showed p-values of 0.203 for the association between fattening food consumption and WHR and 0.275 for BRI. Although no statistically significant association was found, adolescents with excessive fattening food consumption tended to have higher WHR and BRI values than those with normal or deficient consumption. In conclusion, fattening food consumption was not significantly associated with WHR or BRI among adolescents. Nevertheless, excessive consumption of high-fat and high-sugar foods should be monitored because it may increase the risk of central obesity and metabolic disorders. ABSTRAK Obesitas sentral pada remaja menjadi salah satu masalah kesehatan yang terus meningkat seiring perubahan pola makan dan gaya hidup modern. Konsumsi fattening foods seperti fast food, gorengan, makanan tinggi gula, dan makanan tinggi lemak diduga berkontribusi terhadap peningkatan distribusi lemak tubuh yang diukur melalui Rasio Lingkar Pinggang Pinggul (RLPP) dan Body Roundness Index (BRI). Penelitian ini bertujuan menganalisis hubungan konsumsi fattening foods dengan RLPP dan BRI pada remaja di SMA Negeri Surakarta. Penelitian menggunakan desain observasional analitik dengan pendekatan cross-sectional pada 140 responden yang dipilih menggunakan teknik multistage random sampling di empat SMA Negeri Surakarta. Data konsumsi fattening foods diperoleh menggunakan Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), sedangkan RLPP dan BRI diukur melalui antropometri lingkar pinggang, lingkar panggul, dan tinggi badan. Analisis data dilakukan secara deskriptif dan bivariat menggunakan uji Pearson Product Moment atau Rank Spearman sesuai distribusi data. Hasil menunjukkan nilai p=0,203 untuk hubungan konsumsi fattening foods dengan RLPP dan p=0,275 dengan BRI. Meskipun demikian, responden dengan konsumsi fattening foods berlebih cenderung memiliki nilai RLPP dan BRI lebih tinggi dibandingkan kelompok konsumsi normal dan defisit. Kesimpulannya, konsumsi fattening foods tidak berhubungan signifikan dengan RLPP maupun BRI pada remaja. Namun, konsumsi makanan tinggi lemak dan gula tetap perlu diperhatikan karena berpotensi meningkatkan risiko obesitas sentral dan gangguan metabolik.